2013
DOI: 10.1111/boj.12065
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Betulaceae sequences from GenBank to generate a new chronogram for the family

Abstract: Betulaceae, with 120–150 species in six genera, are a family of Fagales that occurs mainly in the Northern Hemisphere. Previous studies of the evolution of Alnus, Betula, Carpinus, Corylus, Ostrya and Ostryopsis have relied on a relatively small number of sequence data and molecular clocks with fixed‐point calibrations. We exploited GenBank to construct Betulaceae matrices of up to 900 sequence accessions and 9300 nucleotides of nuclear and plastid DNA; we also computed species consensus sequences to build 46‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 63 publications
6
43
0
Order By: Relevance
“…Using secondary dating constraints and age priors based on outgroup fossils typically leads to overly young age estimates (e.g. Grimm & Renner, 2013, for Betulaceae; Garzón-Orduña et al, 2015, for Solanaceae and Ithomiini; Schenk, 2016, for simulated data). For example, in the two families of Canellales, namely Canellaceae and Winteraceae, crown group estimates using ingroup fossils as age priors are about double the age of those inferred based on a large magnoliid dataset including only root age constraints for the Winteraceae and the order (Marquínez et al, 2009; Thomas et al, 2014; Massoni, Couvreur & Sauquet, 2015; Müller et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Using secondary dating constraints and age priors based on outgroup fossils typically leads to overly young age estimates (e.g. Grimm & Renner, 2013, for Betulaceae; Garzón-Orduña et al, 2015, for Solanaceae and Ithomiini; Schenk, 2016, for simulated data). For example, in the two families of Canellales, namely Canellaceae and Winteraceae, crown group estimates using ingroup fossils as age priors are about double the age of those inferred based on a large magnoliid dataset including only root age constraints for the Winteraceae and the order (Marquínez et al, 2009; Thomas et al, 2014; Massoni, Couvreur & Sauquet, 2015; Müller et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Data on Loranthaceae (in total 711 accessions) were harvested using the NCBI GenBank portal (accessed 3 April 2014) following the procedure outlined in Grimm and Renner (2013): GenBank flatfiles were read-out with gbk2fas (Göker et al 2009), data aligned using mafft (Katoh et al 2005; Katoh & Standley 2013) and visual inspections and curation of alignments done using Mesquite v. 2.75 (Maddison & Maddison 2011). The set-up and curation details can be found in File S2.…”
Section: Methodsmentioning
confidence: 99%
“…and Ostryopsis sp.). [13] This family members are mainly distributed in northern temperate zone and usually characterized with their stipulate, doubly serrate leaves, catkins and small winged fruits or nuts with leafy bracts. [14,15] Ostrya, which is a genus in Betulaceae family, comprises the several species, including O. carpinifolia (European hophornbeam), O. virginiana (Eastern hophornbeam), O. chiosensis (Chisos hophornbeam) and O. knowltonii (Knowlton hophornbeam), [16,17] which are native to Mexico, Eurasia, eastern Asia/Japan, USA and Canada.…”
Section: Introductionmentioning
confidence: 99%
“…[26] However, the number of genetic studies about this species is still limited, although some of its relatives were reported in phylogenetic analyses. [13,15,27] Traditional assessments of plant systematics or phylogeny were mainly based on the analyses of anatomical and morphological characteristics of plants, which are usually affected by plant habitat and variability. [28] However, molecular markers are now commonly used in systematics studies, as well as in genetic diversity assessments in plants.…”
Section: Introductionmentioning
confidence: 99%